Intussusception of the distal bowel after ileostomy - Jinbao Han; Gang Liu; Qiao Xia; Liuming Huang (Elsevier, 2022)
Postoperative intussusception (POI) in preterm infants is very rare; intussusception at the distal end of the stoma is not seen. A 13-day-old premature infant was referred from peripheral hospital with history of necrotizing enterocolitis(NEC), which after the surgery of enterostomy. No typical symptoms appeared during treatment. Distal intestinal intussusception found during closed enterostomy. The patient recovered well after excision of the intussusception and intestinal anastomosis.